A New Species of Pinguicula (Lentibulariaceae) from Western Yunnan, China (Bangladesh Journal of Plant Taxonomy, 2023)
A new species of Lentibulariaceae, Pinguicula gongshanensis, is described and illustrated from western Yunnan, China. Morphologically, it is similar to Pinguicula alpina but differs from the latter by its corolla with 8–12 brown stripes on the tube and spur, yellow corolla lip, corolla tube with yellow pubescence inside, glandular pilose pedicel, and calyx.Bangladesh J. Plant Taxon. 30(2): 171-174, 2023 (December)